Removal of Heavy Metals: Pb(II), Ni(II) And Cd(II) By Fe3O4@SiO2-TMPDT Adsorbent Prepared From Rice Husk Ash - Sri Hastuti; Tri Martini; Atmanto Heru Wibowo; Dina Fitriana; Wihda Zuhara; Rima Indriyana Putri; Hesti Mutma'inah (UNIVERSITAS SEBELAS MARET (UNS), 2025)
The adsorption of Pb(II), Ni(II), and Cd(II) metal ions onto Fe3O4@SiO2-TMPDT adsorbent was carried out through batch experiments. In this study, Fe3O4@SiO2-TMPDT adsorbent was synthesized through a sol-gel process using sodium silicate extracted from rice husk ash (Na2SiO3)RHA with the addition of magnetite (Fe3O4) and modifier N1-(3-trimethoxysilylpropyl) diethylenetriamine (TMPDT). The synthesized adsorbent was then characterized by FTIR. The Fe3O4@SiO2-TMPDT adsorbent was prepared with suspension Fe3O4:(Na2SiO3)RHA ratios (v/v) of 1:4, 2:3, and 1:1, and varying the amounts of TMPDT of 1; 2.5 and 5 mL. The optimum pH to perform conditions adsorption for Pb(II) metal ions was determined to be 4, while Ni(II) and Cd(II) were 5. In addition, the adsorption process followed a pseudo-second-order kinetic model, and the adsorption isotherm was consistent with the Langmuir isotherm. The adsorption capacities for Pb(II), Ni(II), and Cd(II) were 11.760 mg/g, 1.864 mg/g, and 1.888 mg/g, respectively.